A bimetal hierarchical layer structure MOF grown on Ni foam as a bifunctional catalyst for the OER and HER. Issue 11 (27th April 2021) - Mou, Qiuxiang; Xu, Zhenhang; Wang, Guannan; Li, Erlei; Liu, Jinyan; Zhao, Pingping; Liu, Xinghai; Li, Houbin; Cheng, Gongzhen
Abstract : The as-synthesized NiFe-MOF-5 exhibited an overpotential of 168 mV at 10 mA cm −2 for OER and a voltage of 1.57 V at 10 mA cm −2 for overall water splitting, outperforming most non-noble metal catalysts reported in 1 M KOH. Abstract : NiFe-based non-precious-metal catalysts are promising substitutes for noble-metal-based catalysts due to their outstanding electrochemical performance and endurance. Herein, a NiFe-based MOF supported on Ni foam was designed to obtain good OER and HER activities in alkaline media. Thanks to the 3-D hierarchical layer structure distributed on Ni foam, the high exposure of active sites, and the good conductance, as-obtained NiFe-MOF-5 presented advantages for its use in electrochemical catalysis. As a result, an overpotential of 168 mV at 10 mA cm −2 for the OER was reached. Moreover, the catalyst only required a cell voltage of 1.57 V at 10 mA cm −2 for overall water splitting, and it outperformed most previously reported non-precious-metal electrocatalysts in 1 M KOH.